Generalist and Specialist Mite Herbivores Induce Similar Defense Responses in Maize and Barley but Differ in Susceptibility to Benzoxazinoids - Bui, Huyen; Greenhalgh, Robert; Ruckert, Alice; Gill, Gunbharpur S.; Lee, Sarah; Ramirez, Ricardo A.; Clark, Richard M. (Frontiers in Plant Science, 2018)
While substantial progress has been made in understanding defense responses of cereals to insect herbivores, comparatively little is known about responses to feeding by spider mites. Nevertheless, several spider mite species, including the generalist Tetranychus urticae and the grass specialist Oligonychus pratensis, cause damage on cereals such as maize and wheat, especially during drought stress. To understand defense responses of cereals to spider mites, we characterized the transcriptomic responses of maize and barley to herbivory by both mite species, and included a wounding control against which modulation of defenses could be tested. T. urticae and O. pratensis induced highly correlated changes in gene expression on both maize and barley. Within 2 hours, hundreds of genes were upregulated, and thousands of genes were up- or downregulated after 24 hours. In general, expression changes were similar to those induced by wounding, including for genes associated with jasmonic acid biosynthesis and signaling. Many genes encoding proteins involved in direct defenses, or those required for herbivore-induced plant volatiles, were strongly upregulated in response to mite herbivory. Further, biosynthesis genes for benzoxazinoids, which are specialized compounds of Poaceae with known roles in deterring insect herbivores, were induced in maize. Compared to chewing insects, spider mites are cell content feeders and cause grossly different patterns of tissue damage. Nonetheless, the gene expression responses of maize to both mite herbivores, including for phytohormone signaling pathways and for the synthesis of the benzoxazinoid 2-hydroxy-4,7-dimethoxy-1,4-benzoxazin-3-one glucoside (HDMBOA-Glc), a known defensive metabolite against caterpillars, resembled those reported for a generalist chewing insect, Spodoptera exigua. On maize plants harboring mutations in several benzoxazinoid biosynthesis genes, T. urticae performance dramatically increased as compared to wildtype plants. In contrast, no difference in performance was observed between mutant and wildtype plants for the specialist O. pratensis. Collectively, our data provide little evidence that maize and barley defense responses differentiate herbivory between T. urticae and O. pratensis. Further, our work suggests that the likely route to specialization for O. pratensis involved the evolution of a robust mechanism to cope with the benzoxazinoid defenses of its cereal hosts.